Is Cystatin C a powerful Predictor of Cardiovascular Diseases in patients with type 2 Diabetes Mellitus? (Study on Egyptian patients) - Hesham Rafat, Sameh H. Soror, Zeinab Hassan, Ashref Ismaail (Journal of Applied Pharmaceutical Science)
Cystatin C is a non-glycosilated protein. It is used mainly as a biomarker of renal functions. Diabetes mellitus has been associated with serious complications. Diabetic nephropathy is the main risk factor for morbidity in diabetes mellitus. This study was conducted to assess the clinical value of Cystatin C (CysC) in the diagnosis of cardiovascular complications and diabetic nephropathy in type 2 Egyptian diabetic patients. Serum CysC level was determined in three groups of patients; Diabetics, diabetic nephropathy and diabetic cardiovascular, using ELIZA technique. CysC showed higher sensitivity in early kidney dysfunction and the different stages of nephropathy relative to the control group. C-reactive protein (CRP) showed significant difference in diabetic hypertensives group and in diabetic hypertensives suffering cardiac problems when compared to the control. We found that CysC had higher sensitivity, specificity and area under the curve than creatinine, microalbuminuria and CRP CysC is one of the most efficient markers for diagnosis of diabetic complications and may be used to assess mild kidney impairment in healthy individuals with high muscle mass.
Keywords: Diabetic complications, Cystatin C, microalbuminuria, ACR, CRP, and GFRCys.